{Labial fusion in adolescence secondary to lichen sclerosus} - Kalampalikis, A.; Ivanidou, S.; Michala, L. (Journal of Obstetrics and Gynaecology, 2020)
© 2020 Informa UK Limited, trading as Taylor {&} Francis Group. Labial fusion in adolescence is uncommon and is usually secondary to other skin disorders or trauma of the vulvar area. In a five-year period, we treated five patients with labial fusion in our facility with a mean age of 16.4 years. Based on clinical presentation and biopsy of the vulvar skin, lichen sclerosus (LS) was the causative factor. Four out of five had urinary problems and one suffered from an inflamed inclusion cyst. All of them had a long history of pruritus. In all cases, blunt separation of the labia minora under general anaesthesia was performed, followed by local application of a potent glucocorticoid cream and an emollient agent. One patient received additionally oral and local antibiotics. One recurrence was noted, which resolved after re-separation and more meticulous treatment. Early identification and treatment of LS are crucial to prevent distortion of the vulvar anatomy.Impact StatementWhat is already known on this subject? Labial fusion is an uncommon problem in adolescence and an underlying cause should always be investigated. Lichen sclerosus typically affects the anogenital area and can lead to fusion of the labia minora. What do the results of this study add? Urinary symptoms may be the presenting feature of LS in adolescents. What are the implications of these findings for clinical practice and/or further research? Delay in diagnosis and appropriate treatment can result in irreversible changes to the vulva.
Keywords: adhesion; adolescence; agglutination; fusion; Labia; lichen sclerosus